LEARNING OBJECTIVES OF ISLAMIC RELIGIOUS EDUCATION IN SCHOOLS: THE ROLE OF THE TEACHER AND ITS IMPLICATIONS BASED ON RELEVANT STUDY - Naofa, Muhammad l; Zahari, Iqlima; Maq, Mumu Muzayyin; Sidik, Jafar; Kholik, Nur; Muhammad, Hasman Zhafiri (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The paper aims to determine the learning objectives of Islamic religious education in schools. The research design used is the literature review method. Literature study (literature review) is research carried out by researchers by collecting a number of books and magazines related to the problem and research objectives. This technique is carried out with the aim of uncovering various theories that are relevant to the problems being faced/researched as reference material in discussing research results. The results of this study are that religious education teachers are professional educators with the main task of educating, teaching, guiding, directing, training, modeling, assessing and distributing students.